Q-switched ytterbium-doped fiber laser with zinc oxide based saturable absorber. (20th October 2016) - Ahmad, H; Salim, M A M; Ismail, M F; Harun, S W
Abstract: A Q-switched ytterbium doped fiber laser (YDFL) with a ZnO saturable absorber (SA) is used to demonstrate the generation of pulses in the 1 micron region. The system has a Q-switching threshold of approximately 115.2 mW, and can generate pulses with a 3.0 µ s full-width at half maximum as well as a peak-to-pedestal ratio of 53.0 dB. No spectral modulations are observed, indicating a highly stable system. The pulse output of the proposed system has repetition rates and pulse widths of approximately 50 kHz and 1.6 µ s, as well as an average output power of 0.14 mW and a pulse energy of 2.8 nJ at its highest pump power of 196 mW. This is the first time, to the authors' knowledge, that a ZnO based SA has been used to generate pulses in the 1 micron region with a YDFL.